Associations Between Women's Perception of Their Husbands'/Partners' Social Support and Pap Screening in Pacific Islander Communities. (January 2016) - Mouttapa, Michele; Park Tanjasiri, Sora; Wu Weiss, Jie; Sablan-Santos, Lola; DeGuzman Lacsamana, Jasmine; Quitugua, Lourdes; Flores, Preciosa; Flores, Peter; Paige, Ciara; Tui'one May, Vanessa; Tupua, Marina; Schmidt-Vaivao, Dorothy; et al.
Pacific Islanders experience high rates of cervical cancer incidence and mortality. This cross-sectional study examined the extent to which Samoan, Chamorro, and Tongan women's perceived receipt of social support from their husbands or male partners was associated with rates of routine cancer screening- specifically Pap testing. A total of 585 Pacific Islander women who live in the United States completed a self-report survey. Women who reported having a Pap test within the past 3 years had significantly higher scores on support from their husbands/male partners. Furthermore, the relationship of emotional support and informational support with increased Pap testing was significantly stronger for Tongan women. The findings suggest that men play an important role in promoting women's cancer prevention behaviors in Pacific Islander and potentially other collectivistic populations. Incorporating social support messages into interventions may be a simple yet effective strategy to increase women's Pap testing.